Effect of Water Stress and Levels of Bio-Organic Fertilizers on Water Productivity and Potato Solanum tuberosum L. Yield - Tareq K. Masood; Alaa S. Ati; Qusai O. Hammadi (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2023)
A field experiment was conducted at the University of Baghdad, Al-Jadriya in the spring season of 2021 for the potato crop under the influence of organic biofertilizers and water stress. Three levels of bio-organic fertilizers were used 0 (OM0), 1 (OM1) and 1.5 (OM2) ton ha-1 and three levels of irrigation 30 (I-30), 50 (I-50) and 75 (I-75) % water depletion were available to evaluate the role of bio-organic fertilizer and water stress in production functions and water use efficiency. I-30 treatment showed the highest water consumption ranging between 468 and 486 mm season-1 and decreased to 355-436 mm with water stress treatments I-75. The values of water consumption varied according to the levels of bio-organic fertilizer. The percentage of decrease in water consumption was 1.49 and 3.66% at low stress and reached 6.37% at high stress (I-75) compared to OM0. Both treatments I-30 and I-50 gave the same yield. Bio-organic fertilization led to an increase in the average yield of tubers 32.8 and 41.9% for both OM1 and OM2 compared to OM0. The production functions indicate that the yield increases by 0.057 ton ha-1 mm-1 of added water, and the water depth must be greater than 64.2 mm to obtain a yield that is 1.96 ton ha-1 more (significant limit) than the treatments in the experiment (1.96=0.057(Irr.). )-1.70). Fertilizer levels are higher than 1.9 ton ha-1 to obtain a higher yield of tubers by 26.29 tons/ha and the efficiency of water use is nil according to the water use function when the water consumption is higher than 692.7 mm. The response factor decreased when adding bio-organic fertilizer compared to OM0, which means that plants were not affected significantly under water stress conditions.